The Antioxidant System of the Respiratory Tract. The Intracellular Antioxidant Protection in the Respiratory Tract (Part 4) - A.E. Abaturov; A.P. Volosovets; T.P. Borysova (Zaslavsky O.Yu., 2016)
In the literature review, the current data about the thioredoxin system in the functioning of the intracellular antioxidant protection in the respiratory tract are outlined. The details of thioredoxin-dependent oxidation reaction are described. Other physiological effects of thioredoxin system - antiapoptotic and proinflammatory action are presented.